The relationship between tooth loss, body mass index, and hypertension in postmenopausal female - Mustafa Al-Ahmad, Basma Ezzat; Kashmola, Muhanad Ali Hamdon; Mustafa, Nazih Shaban; Hassan, Haszelini; Arzmi, Mohd Hafiz (Wolters Kluwer - Medknow, 2018)
Objective: This study aimed to investigate the relationship between tooth loss and the level of blood pressure with the hypothesis that tooth loss is associated with the increase of hypertension in postmenopausal women. Materials and Methods: Sixty postmenopausal female patients aged 51–68 years were included in the study to assess the relationship between tooth loss and the level of blood pressure. The information including sociodemographics, last menstruation period, hypertension history, and the duration of having tooth loss was recorded. Blood pressure was measured using sphygmomanometer and the number of tooth loss was determined. Results: The results showed a more significant tooth loss in hypertension (median: 23 + 4; interquartile range [IQR]: 6) compared to the normotension postmenopausal women (median: 18 + 6; IQR: 12; P < 0.05). Furthermore, obese patients had more tooth loss (median: 23 + 5; IQR: 8) than the overweight patients (median: 19 + 8; IQR: 8). Conclusion: Tooth loss is associated with the increase of hypertension in postmenopausal women which may have a role in the development of vascular diseases.